1969
DOI: 10.1073/pnas.64.1.374
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Chondroitin Sulfate-Protein Linkage Region: Purification and Properties of a Glucuronosyltransferase From Embryonic Chick Brain

Abstract: Abstract.-The present paper describes the purification and properties of a glucuronosyltransferase isolated from 13-day embryonic chick brain. The enzyme catalyzes transfer of glucuronic acid from UDP-glucuronic acid to a series of low and high molecular weight compounds which contain terminal nonreducing f-D-galactose residues. Studies utilizing enzymatically degraded chondromucoprotein as acceptor suggest that the glucuronosyltransferase terminates biosynthesis of the linkage region between protein and polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
(1 reference statement)
1
12
0
Order By: Relevance
“…GalL1-3GalL1-4Xyl) but also to disaccharides with analogous structures such as lactose (GalL1-4Glc) and N-acetyllactosamine (GalL1-4GlcNAc) [8,11,12]. In strong contrast, neither lactose nor N-acetyllactosamine was utilized by the recombinant enzyme in the present study (Table 1).…”
Section: Acceptormentioning
confidence: 75%
See 1 more Smart Citation
“…GalL1-3GalL1-4Xyl) but also to disaccharides with analogous structures such as lactose (GalL1-4Glc) and N-acetyllactosamine (GalL1-4GlcNAc) [8,11,12]. In strong contrast, neither lactose nor N-acetyllactosamine was utilized by the recombinant enzyme in the present study (Table 1).…”
Section: Acceptormentioning
confidence: 75%
“…GlcAT-I activity was ¢rst detected in an embryonic chick cartilage extract [8] and was subsequently partially puri¢ed from embryonic chick brain [11] and mouse mastocytoma cells [12]. However, attempts to purify GlcAT-I to homogeneity have not been successful due to the low concentrations and the di¤culty in solubilizing the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these microsomal preparations have been shown to contain GlcA transferase activity for adding GlcA to non-reducing terminal Gal residues such as that found in the Gal-Gal-Xyl linkage region (25,26). Mixed substrate experiments have indicated that the transfers of [ 14 C]GlcA to the linkage oligosaccharide and to chondroitin oligosaccharide are each catalyzed by separate enzymes (25), which have been termed GlcA transferase I and GlcA transferase II (2).…”
mentioning
confidence: 99%
“…This intermediate serves as the primer for heparan sulfate and chondroitin sulfate assembly, which arises from the alternating addition of ␤-GlcNAc and ␤-GlcUA or ␤-GalNAc and ␤-GlcUA residues, respectively, to the linkage tetrasaccharide. Three GlcUA-transferases are thought to catalyze the addition of GlcUA: one involved in the formation of the linkage region tetrasaccharide (GlcUAT-I) (11,12) and two that polymerize the different chains (13). The latter activities may be part of bifunctional enzymes in which the same protein catalyzes the alternating addition of a HexNAc residue and GlcUA (14,15).…”
mentioning
confidence: 99%